College achievement and earnings - Jonathan Gemus (Uppsala University, Department of Economics, 2010)
I study the size and sources of the monetary return to college achievement as measured by cumulative Grade Point Average (GPA). I first present evidence that the return to achievement is large and statistically significant. I find, however, that this masks variation in the return across different groups of people. In particular, there is no relationship between GPA and earnings for graduate degree holders but a large and positive relationship for people without a graduate degree. To reconcile these results, I develop a model where students of differing and initially uncertain ability levels choose effort level in college and whether to earn a graduate degree. College achievement and graduate attainment are allowed to increase human capital and be used by employers to screen workers. In the separating equilibrium studied, workers who earn a graduate degree can effectively signal high productivity to employers. As a result, employers use undergraduate GPA-a noisy signal of productivity-to screen only the workers who do not hold a graduate degree. Viewing the empirical results through the lens of this equilibrium, the zero GPA-earnings relationship for graduate degree holders and the positive and large relationship for people without a graduate degree suggests that most of the reutrn to achievement net of graduate educational attainment is driven by sorting.
urn:nbn:se:uu:diva-112808
Keywords: 330; Bildungsabschluss; Absolventen; Bildungsertrag; Humankapital; Personalauswahl; USA